노인 영양지수 (NQ-E)를 이용한 서울 일부지역 노인의 식생활 및 영양 상태 평가 - 함선욱(Sun-Wook Ham); 김경희(Kyung-Hee Kim) (Journal of nutrition and health, 2020)
Purpose: This study evaluated the dietary quality and nutritional status of elderly people using the Nutrition Quotient for Elderly (NQ-E). Methods: The participants were 204 elderly people over 65 years of age (38 men and, 166 women) in Seoul. The dietary information was analyzed using a questionnaire of NQ-E, which consisted of 19 checklist items, and 24-recall test data. The NQ-E scores and its four factors, including 'balance', 'moderation', 'diversity', and 'dietary behavior' factors, were calculated according to general characteristics of the subjects. The subjects were divided into the 'monitoring needed group' (62 > NQ-E score) and the 'good group' (62 ≤ NQ-E score) according to their NQ-E score. Results: The mean NQ-E score of the total subjects was 61.9, which was within the mediumhigh grade. The scores of balance, moderation, and dietary behavior factors were within the medium-high grade, while the score of the diversity factor was within the medium-low grade. The NQ-E score was 54.8 in the monitoring needed group and 69.3 in the good group. For the score of the diversity factor, the elderly living alone had a significantly lower score than the score for the elderly living with a spouse. The female subjects showed significantly higher scores of moderation and dietary behavior factors than did the male subjects. The daily intakes of vitamin A, thiamin, riboflavin, vitamin C and calcium in the monitoring needed group were significantly lower than those in the good group. The nutrient adequacy ratios (NAR) of vitamin A, thiamin, riboflavin, vitamin C and calcium in the monitoring needed group were significantly lower compared to the scores of the good group. The indexes of nutritional quality (INQ) of vitamin A, thiamin, riboflavin, vitamin C, calcium and potassium were less than 1 for all the subjects. The monitoring needed group had a significantly lower consumption of total foods, vegetables and mushrooms than the good group. As a result, the nutritional status of the monitoring needed group was significantly lower than that of the good group. Conclusion: The results of this study show that NQ-E would be a useful tool for assessing the dietary quality of the elderly. In conclusion, a focused-nutrition education program and a useful guideline are needed for promoting the health and nutritional status in elderly people. 본 연구대상자의 평균 나이는 78.6세로 75세 이상이 75.0%를 차지하였으며, 만성질환을 2개 이상 갖고 있는 노인이 55.4%였다. 가구 유형에서 독거노인의 비율이 40.7%였고, 70.6%의 노인이 식사 준비를 본인이 하는 것으로 나타났다. 전체 대상자의 평균 NQ-E 점수는 61.9점으로 전국 단위 조사와 비교하면 '중상'에 속하였다. 균형, 절제, 식행동 영역은 전국 단위 조사의 '중상'에 속하였고 다양 영역은 '중하'에 속하였다. 여자노인이 남자노인보다 절제와 식행동 영역의 점수가 높았다. 독거노인은 배우자동거노인에 비해 다양성 영역의 점수가 낮았다. 다양성 영역은 소득과 교육수준이 높은 노인의 점수가 높았고, 절제 영역은 소득수준이 낮은 노인과 2개 이상의 만성질환을 보유하고 있는 노인의 점수가 높았다. 영양 보충제를 1개 이상 섭취하는 노인이 영양지수 총점수와 균형, 다양성 및 식행동 영역의 점수가 높았다. 연구 대상자의 51.0%가 모니터링 필요군으로 영양지수 평균은 54.8점이었고, 양호군은 49.0%로 영양지수는 69.3점으로 유의하게 높았다. 본 연구대상자의 에너지, 니아신, 리보플라빈, 비타민 A의 섭취량이 EAR 미만으로 나타났고, 비타민 A, 니아신, 비타민 C, 칼슘 등은 영양권장량 대비 75% 미만으로 섭취하고 있었다. 모니터링 필요군의 1일 에너지 섭취량과 단백질, 티아민, 리보플라빈 및 비타민 C 섭취량이 양호군에 비해 유의하게 낮았다. 또한 모든 영양소의 영양소 적정섭취비 (NAR)가 1 미만이었으며, 모니터링 필요군이 양호군에 비해 비타민 A, 티아민, 리보플라빈, 비타민 C, 칼슘 및 칼륨의 NAR이 유의하게 낮았다. 비타민 A, 리보플라빈, 니아신, 비타민 C, 칼슘, 칼륨의 INQ가 1보다 낮아 에너지 섭취량에 비해 부족한 영양소로 나타났다. 1일 식품섭취량에서 모니터링 필요군이 양호군에 비해 총 식품 섭취량과 채소류 및 버섯류 섭취량이 유의적으로 낮았다. 본 연구 결과 노인 영양지수가 높은 군이 낮은 군보다 24시간 회상법으로 조사한 식품섭취조사에서 단백질을 비롯한 대부분의 필수영양소 섭취 수준이 유의적으로 높은 것으로 나타나서, NQ-E가 노인의 식생활 및 영양 상태를 평가할 수 있는 타당한 도구임을 보여준다.